Influence of Work Motivation, Compensation and Organizational Commitment Towards Employee Retention at STIKES Surya Global - Ruslarta; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of work motivation, compensation and organizational competence on STIKES Surya Global employee retention. The sample in this study was 45 respondents. The data collection technique used is a survey method with the research instrument used is a questionnaire. The instrument test results stated that the data in this study was proven to be valid and reliable. The classical assumption test states that the data in this study is normally distributed and produces a regression that is free from multicollinearity and heteroscedasticity. The results of the multiple linear regression test, t test (partial), F test (simultaneous), and coefficient of determination show that partially: (1) Work motivation has a significant positive effect on STIKES Surya Global employee retention, (2) Compensation has a positive and significant effect on employee retention. STIKES Surya Global employee retention, (3) Organizational commitment has a positive and significant effect on STIKES Surya Global employee retention.